Le droit de punir - Rico, José (Criminologie, 1986)
The main objective of this essay is to put forward some ideas in the right to punish. These ideas are put in the Canadian context and in relation to the criminal law. The criminal procedure and the criminal justice system. The first part defines the proper concepts : aims, justifications, scopes, limits and interconnections. Results cannot be properly evaluated if the basic definitions are not clear and precise. The second part presents a model for the revision and reform of criminal policies and practices. This model is based on a study of drug legislations and practices.